Projeto - Vida de formiga - Stupp, Iris Juliana Viotto; Carraro, Marcia Regina Simpioni; Dias, Elorita Katia Malvezzi; Carraro, Márcia; Oliveira, Maria Auxiliadora de (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> VER PDF